(3GdCUhd GdYdejI aj GdbhGFe GdeMGSHjI hGdeGdjI (B/s - (3YHOg, LdGd MSfs ((3YeGf(B: s (3OGQ RgQGf ddWHGYI(B, s, 2006)
(3jVe ehGRjf GdeQGLYI hGdbhGFe GdeGdjI GdeMGSHjI , JMVjQ GdMSGHGJ GdNJGejI , YQV GdbhGFe GdeGdjI GdeMGSHjI , GdeHGOF GdeMGSHjI hGdbhGFe GdeGdjI , GdJShjGJ GdLQOjI ddMSGHGJ GdhgejI , GdJShjGJ heHOC GdebGHdI , GdJShjGJ GdLQOjI dMSGHGJ GdeUQhaGJ ,GdJShjGJ GdLQOjI dMSGHGJ GdGjQGOGJ GdeMGSHI Ydi GdCUhd GdeJOGhdI , GdeMGSHI Ydi GdfbOjI aj GdUfOhb , GdMSGHGJ GdHfcjI , GdeMGSHI Yf GdeOjhfjf , GdeMGSHI Ydi ChQGb GdbjV , GdeMGSHI Yf GdGSJKeGQGJ aj GdChQGb GdeGdjI MSGHGJ GdeNRhf GdSdYj(B. s
Keywords: (3GdeGdjI GdYGeI(B- (3eMGSHIs; (3GdeMGSHI GdEOGQjIs; (3eMGSHIs